Effect of Temperature and Duration of Maceration on Colour and Sensory Properties of Red Wine - A Review - Şener, H. (South African Journal of Enology and Viticulture, 2018)
The maceration process plays an important role in the composition of the colour and sensory properties of red wine by facilitating the extraction of phenolic and aromatic compounds found in grapes. This review summarises the key findings from a study of the literature associated with research on the effects of the temperature and duration of maceration on the phenolic content, colour and sensory properties of red wine. In the past, many researchers have reported that higher maceration temperatures increase the extraction of phenolic compounds and enhance red wine colour, but low-temperature pre-fermentative techniques have become more popular in recent years due to their positive effects on wine composition, including lower oxidation of anthocyanin pigments and aroma compounds, inhibition of undesirable enzymatic activities, and an environment that is less conductive to microbial growth. Macerations carried out at low temperature ranges (10°C to 15°C) result in red wines with the highest levels of total phenolic content, anthocyanin and colour intensity, and richer fruity, flowery and spicy aroma. The duration of maceration has also been shown to have significant effects on red wine phenolic compounds, colour properties and the relevant sensory attributes. Studies show that prolonged maceration leads to a stable red colour, as well as richer tannin content, polymeric pigments and astringency. Red wines with appropriate colour and sensory characteristics can be produced by adapting both maceration temperature and duration to the desired style.